Modelling of Deep-Sea Gravity Currents Using an Integrated Plume Model - Alendal, Guttorm; Drange, Helge; Haugan, Peter M (The Polar Oceans and Their Role in Shaping the Global Environment, 1994)
An integrated plume model is used to describe large scale gravity currents in the ocean. The model describes competing effects of (negative) buoyancy, friction, entrainment and Cariolis farce, as well as a pressure term due to variable plume thickness, on the flux, speed and flow direction of the plume. Equations for conservation of salt and internal energy (temperature) and a full equation of state far seawater is included in the model. The entrainment of ambient water is parameterized with support in empirical data, and a drag coefficient consistent with the entrainment is introduced. The model is tested against the overflow through the Denmark Strait, the flow down the Weddell Sea continental slope, and the outflow of saline water through the Gibraltar Strait and from the Spencer Gulf, Australia. The farmer gain an extra driving mechanism due to the thermobaric effect, while in the two latter cases the initial density difference is so large that this effect is not essential. Order of magnitude fit with measurements requires drag coefficient between 0.01 and 0.1. Conditions susceptible to meander behaviour and a singularity arising from the pressure dependency on the current thickness variations are briefly discussed.
Keywords: Sørishavet; Weddellhavet; havbunnen; havstrømmer; klimamodeller; oseanografi